Temperature Effect on "Ragone Plots" of Lithium-Ion Batteries. Issue 3 (1st January 2018) - Kumar, S. Krishna; Abduh, Audy A. B. M.; Sabih, Othmane; Yazami, Rachid
Abstract : Temperature is a major factor affecting lithium-ion batteries (LIB) performances including power, energy and life. Energy density vs. power density ( E ( P )) charts known as "Ragone plots" are convenient charts for comparing the performance of energy storage systems (ESS) such as batteries, supercapacitors, fuel cells, flywheels, hydrogen and gasoline. Basically, Ragone plots allow one to determine the amount of energy E (Wh kg −1 and Wh l −1 ) an ESS may deliver under a constant power load P (W kg −1 and W l −1 ). In this study Ragone charts are achieved on commercial LIB cells at temperatures ranging from −20°C to + 55°C. Cells are first charged using CCCV protocol at C/10 up to 4.2 V at the ambient temperatures (∼25°C). Then cells are discharged isothermally at constant rates ranging from C/5 to 10 C. To account for varying power and temperature Ragone isotherms are integrated over the power range yielding a functional Integrated Energy-Power ( ∫ P E ( P ) d P ∣ T 2 ) . The ratio of integrated areas at T and at 25°C gives the "Energy-Power Index" (EPI) (%). The EPI vs. T profile shows a linear increase between −10°C and 25°C then it makes a semi-plateau between 25°C and 55°C.